1999
DOI: 10.1081/clt-100102451
|View full text |Cite
|
Sign up to set email alerts
|

Position Statement and Practice Guidelines on the Use of Multi-Dose Activated Charcoal in the Treatment of Acute Poisoning

Abstract: In preparing this Position Statement, all relevant scientific literature was identified and reviewed critically by acknowledged experts using agreed criteria. 1-124 Well-conducted clinical and experimental studies were given precedence over anecdotal case reports and abstracts were not usually considered. A draft Position Statement was then produced and subjected to detailed peer review by an international group of clinical toxicologists chosen by the American Academy of Clinical Toxicology and the European As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(8 citation statements)
references
References 104 publications
0
7
0
Order By: Relevance
“…The number of digestive decontaminations performed in this study was high compared to the records published annually by the American Association of Poison Control Centers (AAPCC) ( 27 ). Many studies have revealed that the combination of LG and CA is not more effective than the exclusive administration of CA ( 28 , 29 ). However, in Alcañiz, this association occurred 1 out of 3 times.…”
Section: Discussionmentioning
confidence: 99%
“…The number of digestive decontaminations performed in this study was high compared to the records published annually by the American Association of Poison Control Centers (AAPCC) ( 27 ). Many studies have revealed that the combination of LG and CA is not more effective than the exclusive administration of CA ( 28 , 29 ). However, in Alcañiz, this association occurred 1 out of 3 times.…”
Section: Discussionmentioning
confidence: 99%
“…carbamazepine, or theophylline. Urinary alkalinization can enhance the elimination of salicylates and a few other poisons [16][17][18]. Chelation therapy can also enhance the elimination of selected metals.…”
Section: International Journal Of Scientific Advances Issn: 2708-7972mentioning
confidence: 99%
“…This is a therapeutic inotropic agent/antiarrhythmic with a narrow therapeutic window. It presents with nausea, malaise, weakness, bradycardia, heart block, hyperkalemia, visual complaints of seeing yellow halos around lights[17]. Treatment with digoxin-specific antibody is indicated for hemodynamically compromising conduction disturbances or for hyperkalemia.…”
mentioning
confidence: 99%
“…For dermal contact, surface decontamination with copious amount of water is most effective. For poison ingestion, methods of gastrointestinal (GI) decontamination include gastric lavage, 4 single-dose activated charcoal, 5 multipledose activated charcoal, 6 whole bowel irrigation, 7 and rarely surgical intervention such as endoscopic removal or gastrostomy. In Hong Kong, about 15% of poisoning cases are treated with GI decontamination mostly by oral administration of activated charcoal.…”
Section: Assessment Of Acute Poisoningmentioning
confidence: 99%